Profil bactériologique des otites moyennes en ORL au Centre hospitalier départemental du Borgou au Bénin. - HOUNKPATIN, Spéro; ADJIBABI, WASSI; LAWSON ÉPSE AFOUDA, SONIA RUTH JOSÉPHINE; AVAKOUDJO, FRANÇOIS; CHABI, B; GANDAHO, PROSPER; VODOUHE, SOGBADJI JOSEPH; HOUNKPE, YÉDÉNOU Y. CÉLESTIN (My University, 2009)
......
Keywords: ......